Effects of Placebo Interventions on Subjective and Objective Markers of Appetite–A Randomized Controlled Trial - Hoffmann, Verena; Lanz, Marina; Mackert, Jennifer; Müller, Timo; Tschöp, Matthias; Meissner, Karin (Frontiers in Psychiatry, 2018)
Objective: Patients’ expectations about the benefit of an intervention are important determinants of the placebo effect. Little is known about the extent to which expectations influence outcomes of treatments in the field of appetite regulation. This study aimed to investigate the effects of treatment-related expectations on subjective and objective markers of appetite. Methods: 90 healthy participants of normal weight were randomly allocated to either an appetite-enhancing placebo group, a satiety-enhancing placebo group, or a control group. All participants received a placebo capsule along with group-specific verbal suggestions to either be appetite-promoting, or satiety-enhancing, or to have no effect on appetite. Before and during the 2 hours following randomization, participants were repeatedly asked to rate feelings of hunger and satiety on visual analogue scales (VAS), and blood samples were taken repeatedly to assess plasma ghrelin levels as a physiological marker of hunger. Results: In comparison to the control group, the satiety-enhancing placebo intervention significantly reduced appetite and increased satiety. The appetite-enhancing placebo intervention did not alter subjective levels of hunger, but increased plasma ghrelin levels in females. Conclusions: Results provide the first experimental evidence that appetite-regulating placebo interventions can elicit a psychobiological response. Expectations are important factors to consider when evaluating the effects of interventions in the field of appetite regulation.